Non-Competitive Wage-Setting as a Cause of Unfriendly and Inefficient Leadership - Robert Dur; Ola Kvaløy; Anja Schöttner (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper develops a simple economic model to examine how leadership styles in organizations depend on the prevailing wage-setting conditions for workers. In particular, we examine a leader who can - in addition to the use of monetary incentives - motivate a worker by adopting leadership styles that differ in their non-monetary consequences for the worker's well-being. Some leadership styles produce non-monetary benefits for workers (such as those involving the provision of praise to high-performing workers), other styles impose non-monetary costs (such as those involving social punishment for low performers). We show that leaders never use the latter type of leadership when the worker is hired in a competitive labor market. In contrast, in labor markets with non-competitive wage-setting (e.g., in the presence of trade union bargaining or minimum wage legislation) leaders sometimes do use the `unfriendly' style, and the more so the worse the worker's labor market prospects are. We show that this is socially inefficient. `Friendly' leadership styles are always adopted when they are socially efficient.
Keywords: M50; 330; leadership styles; incentives; motivation; wage-setting